Voice outcome and voice‐related quality of life after surgery for pediatric laryngotracheal stenosis. (9th November 2016) - Pullens, Bas; Hakkesteegt, Marieke; Hoeve, Hans; Timmerman, Marieke; Joosten, Koen
Abstract : Objectives: To evaluate the long‐term outcome of voice quality and voice‐related quality of life after open airway surgery for pediatric laryngotracheal stenosis. Study Design: Prospective cohort study. Methods: Children under the age of 18 years at time of follow‐up and with a history of open airway surgery for acquired laryngotracheal stenosis were included in this analysis. To assess voice‐related quality of life, the pediatric voice handicap (pVHI) index was completed by the patients' parents. The dysphonia severity index (DSI) was used as an objective measurement for voice quality. Results: Fifty‐five parents completed the pVHI, and 38 children completed the DSI. This showed high pVHI values and low total DSI scores, indicating significant voice disturbance. After multivariate analysis, the presence of comorbidities and glottic involvement of the stenosis are associated with poor long‐term voice‐related quality of life. Conclusion: Significant voice disturbance is common after surgery for pediatric laryngotracheal stenosis. Glottic involvement of the stenosis and comorbidities is associated with poor voice‐related quality of life. Evaluation of pre‐ and postoperative voice quality and voice‐related quality of life is advised for children treated for laryngotracheal stenosis. Level of Evidence: 2B. Laryngoscope, 127:1707–1711, 2017